Trends in the prevalence of gestational diabetes mellitus in southern Sweden, 2003–2012. (5th March 2014) - Ignell, Claes; Claesson, Rickard; Anderberg, Eva; Berntorp, Kerstin
Abstract There is accumulating evidence that gestational diabetes is a growing problem. The lack of internationally standardized diagnostic procedures prevents consistent diagnosis and the burden of gestational diabetes must be determined in country‐specific studies. In southern Sweden, gestational diabetes is defined as a 2‐h capillary plasma glucose concentration of ≥10.0 mmol/L during a universal 75‐g oral glucose tolerance test. We report the crude prevalence of gestational diabetes during the years 2003–2012. Of 156 144 women who gave birth, 2.2% were diagnosed with gestational diabetes. When the effect of time on the prevalence of gestational diabetes was assessed in a log‐linear Poisson model, an overall increase in prevalence of 35% was predicted, corresponding to an average annual increase of 3.4%. Predicted prevalence was 1.9 (95% CI 1.8–2.0) in 2003 and 2.6 (95% CI 2.4–2.7) in 2012 (p < 0.0001). Due to a simultaneous rise in birth rate, the number of women diagnosed with gestational diabetes increased by 64%.